Food authentication by PCR-based methods - Mafra, Isabel; Ferreira, Isabel M. P. L. V. O; Oliveira, M. Beatriz P. P (European food research & technology, 2008)
Food authenticity is presently a subject of great concern to food authorities, as the incorrect labelling of foodstuffs can represent a commercial fraud. The implication of misleading labelling can be much more important concerning the presence of potentially allergenic foods. The need to support food labelling has provided the development of analytical techniques for the analysis of food ingredients. In the last years, several methods based on polymerase chain reaction (PCR) have been proposed as useful means for identifying species of origin in foods, as well as food allergens and genetically modified organisms (GMO), due to their high specificity and sensitivity, as well as rapid processing time and low cost. This work intends to provide an updated and extensive overview on the PCR-based methods for food authentication, including also methods for allergens and GMO the detection in foods.